On Social Forecasts Reliability - Guerman Grigoryevich Philippov (Управленческое консультирование, 2018)
An abundance of social forecasts poses as urgent the problem of their assessment as to plausibility and reliability, not waiting for the test of time. Such an assessment is composed not only of an expert judgement based upon the resources and facilities of the corresponding specialized science, but as well as of a well-grounded verdict of a metatheory of a specific branch of scientific knowledge. This metatheory includes world-outlook principles applied, methodological premises, the validity of general scientific methods used as well as logical conformity of the chosen procedures and scientific methodology of cognition. It is possible to make sufficiently reliable estimations of many social forecasts plausibility only on the basis of a metatheory alone.